Aportes para seguir pensando las competencias ciudadanas en los nuevos tiempos de la educación (Memorias Sifored - Encuentros Educación UAN, 2021)
The presented lecture is a deep reflection on the new possibilities and strategies teaching brings in this pandemic of Covid-19. We understand that after this crisis, the education will never be the same; Also, the social behaviors supported by the contributions made by the creation of citizen coexistence established in Colombia since 2004 become a kind of resilience to continue the re-thinking the how we can work in the future in our classrooms and, above all, how we can keep up with our roles and advance in the formation of individuals committed to an inclusive, ethical and civic society.
Keywords: School coexistence; resilience; citizenship; pedagogy; covid-19